Measuring disability in patients with chronic fatigue syndrome: reliability and validity of the Work and Social Adjustment Scale. - Cella, M; Sharpe, M; Chalder, T (2011)
BACKGROUND: Disability is a defining feature of chronic conditions, and it is an increasingly used measure of therapy effectiveness. The Work and Social Adjustment Scale (WSAS) is a simple and clear measure of disability. Although the scale is widely used, no study has yet investigated its psychometric properties in patients with chronic fatigue syndrome (CFS). METHODS: Data from two samples of patients were used, one from a multicenter randomized controlled clinical trial of treatments for CFS (n =639) and the other from a clinic that specializes in CFS (n=384). All patients completed the WSAS as well as other measures. RESULTS: Internal consistency and the Spearman-Brown split-half coefficient values indicated that the scale is reliable. CFS patients who had comorbid diagnoses of depression, anxiety or fibromyalgia had higher WSAS scores. High levels of disability were associated with high number of physical symptoms, severe fatigue, depression, anxiety, poor sleep quality and poor physical fitness, with correlation coefficients ranging between 0.41 and 0.11. Lower scores on the WSAS were modestly associated with better physical functioning as well as higher levels of physical capacity as assessed by a walking test. Sensitivity to change was evaluated in a subgroup of patients who had undergone a course of cognitive behavioral therapy. Disability significantly decreased after therapy and remained stable at follow-ups. CONCLUSION: The WSAS is a reliable and valid assessment tool for disability in patients with CFS.